Clinical study of vesicular mole - Thakur, Harshada Subhash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Vesicular mole is an abnormal condition where there is partly degeneration and partly hyperplastic changes in the young chorionic villi. The purpose of this study is clinical presentation of molar pregnancy, serum β-hCG regression curve and further management. Methods: This was a prospective study undertaken in the Department of Obstetrics and Gynaecology at the tertiary care center for the study period from October 2007 to May 2009 approved by ethical committee. Results: Incidence of vascular mole was 2.5 per 1000 deliveries. 46.15% women were in the age group 20-24 years, 33.33% in the age group 25-29 years and 20.51% were in the teenage group. 58.97% women were between gravidity 2-4. Conclusions: There was a significant association of serum β-hCG >1,00,000 mlU/ml with theca lutein cysts >6 cm. 11.76% women with complete mole had elevated TFT while not a single woman with partial mole had elevated TFTs.